2010
DOI: 10.1016/j.lingua.2009.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Word order in German: A corpus study

Abstract: This paper presents a corpus study of the order between subject and object in German main and embedded clauses. Since prior studies have shown that object-subject (OS) sentences are rare in comparison to subject-object (SO) sentences, for both main and embedded clauses two corpora were assembled: One corpus containing both SO and OS sentences, and a second corpus containing only OS sentences. In accordance with prior work, the rate of OS sentences was low, but the construction of a corpus restricted to OS-sent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
68
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 31 publications
4
68
2
Order By: Relevance
“…Dative experiencers generally show stronger psych effects than accusative experiencers. For languages such as German and Dutch, this intuition has been supported by empirical findings on experiencer-first effects in Kempen and Harbusch (2003), Haupt et al (2008), Bader and Häussler (2010a), Lamers and de Hoop (2014), Lamers and de Schepper (2010), and Verhoeven (2015). Another type of variation is accusative EO verbs, which appear in different aspectual structures.…”
Section: Backward Binding As a Psych Effectmentioning
confidence: 78%
“…Dative experiencers generally show stronger psych effects than accusative experiencers. For languages such as German and Dutch, this intuition has been supported by empirical findings on experiencer-first effects in Kempen and Harbusch (2003), Haupt et al (2008), Bader and Häussler (2010a), Lamers and de Hoop (2014), Lamers and de Schepper (2010), and Verhoeven (2015). Another type of variation is accusative EO verbs, which appear in different aspectual structures.…”
Section: Backward Binding As a Psych Effectmentioning
confidence: 78%
“…In all sentences, the subject preceded the object, thus confirming that NOM ACC is ranked above ANI. Given the rareness of examples of this kind, they probably occurred not at all or only with very low frequency in corpora of the sizes investigated by Hoberg (1997) or Bader & Häussler (2010b), resulting in a premature acception of the schema in (26). The ranking of ANI above NOM DAT is already contained within the word order template in (26), for which -as pointed out above -a large body of corpus evidence is available.…”
Section: Comparison Of Experimental Data To Corpus Resultsmentioning
confidence: 99%
“…Bader & Häussler (2010b) applied the word order template in (26) to their corpus sample and found that for about 90% of all sentences, order was correctly predicted. The same result was obtained when order was predicted from verb semantics, which roughly corresponds to constraints in terms of thematic roles.…”
Section: Comparison Of Experimental Data To Corpus Resultsmentioning
confidence: 99%
See 2 more Smart Citations